A flexible photodetector based on organic semiconductor and preparation method thereof

By spin-coating and heat-crosslinking a mixed solution of polymer, ionic liquid and crosslinking agent on the back of the substrate of the flexible photodetector to form a porous and resistant film, the problem of low light absorption of the flexible organic photodetector is solved, and the detection rate and mechanical stability are improved.

CN115172596BActive Publication Date: 2025-03-07YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210725887.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-23
Publication Date
2025-03-07
Estimated Expiration
2042-06-23

AI Technical Summary

Technical Problem

The flexible organic photodetector has a low light absorption due to the reflection, refraction and absorption of the substrate itself, and the photodetector device has a low photocurrent and a low detection rate.

Method used

Spin coat a mixed solution of polymer, ionic liquid and crosslinking agent on the back of the flexible transparent substrate, perform heat crosslinking and remove uncrosslinked ionic liquid to form a porous resistant film to enhance the transmittance of light.

Benefits of technology

By regulating the proportion of ionic liquid, the transmittance of light and the detection rate of the photodetector are improved, while the mechanical robustness and physical and chemical stability of the polymer surface are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115172596B_ABST
    Figure CN115172596B_ABST
Patent Text Reader

Abstract

The invention discloses a flexible photodetector based on organic semiconductor and a preparation method thereof, which relates to the technical field of photoelectric sensors or flexible electronics. The flexible photodetector comprises, from bottom to top, a porous antireflection film, a flexible transparent substrate, a flexible transparent cathode, a cathode buffer layer, a photoactive layer, an anode buffer layer and an anode; a thermally cross-linked porous polymer antireflection film modification layer is spin-coated on the back of the flexible transparent substrate; the porous polymer film is preliminarily formed by thermal cross-linking to form a polymer uniformly encapsulating an ionic liquid, and then the ionic liquid is washed away to form; the invention introduces a layer of cross-linked polymer porous antireflection film on the back of the flexible transparent substrate, without the need for transfer printing, and has a simple process, which not only effectively enhances the light transmittance and improves the energy conversion efficiency of the detector, but also improves the mechanical robustness and physicochemical stability of the polymer surface through thermal cross-linking, thereby extending the service life of the antireflection film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photoelectric sensors or flexible electronics, and in particular to a flexible photoelectric detector based on organic semiconductors and a preparation method thereof. Background Art

[0002] As a sensor device that converts optical signals into electrical signals through the photoelectric effect, photodetectors are widely used in environmental monitoring, health detection, and image processing. However, with the demand for organic photodetectors for the next generation of wearable devices, the rigid inorganic photodetectors currently on the market cannot be closely integrated with the human body due to limited mechanical flexibility. In contrast, photodetectors based on organic materials are gaining more and more attention in practical applications due to their inherent mechanical flexibility, low cost, easy processing, adjustable photoelectric properties, and good biocompatibility. At present, the main substrates used for flexible photodetectors are PI, PET, PEN, and PES.

[0003] In a flexible photodetector, light can only be absorbed by the absorption layer after it is incident from the air and penetrates the flexible substrate. The reflection and refraction on the surface of the substrate not only affect the light flux, but also form stray light in the device, making the substrate transmittance low. The amount of light absorbed is a key factor affecting the photocurrent of the photodetector. Increasing the transmittance of the substrate can greatly increase the current of the device, thereby improving the energy conversion efficiency of the photodetector. Due to the above factors, the detection rate of the photodetector in the prior art is not high.

[0004] Therefore, a flexible photodetector based on organic semiconductors and a preparation method thereof are needed to solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to provide a flexible photodetector based on organic semiconductors and a preparation method thereof, aiming to solve the problems of low light absorption, low photocurrent and low detection rate of the flexible organic photodetector due to the reflection, refraction and absorption of the substrate itself. A polymer porous anti-reflection film is formed by thermally cross-linking a mixture of a polymer, an ionic liquid and a bis-nitrogen heterocyclic cross-linking agent on the back of a flexible substrate and washing away the uncross-linked ionic liquid. The present invention does not require transfer printing and has a simple process. By regulating the proportion of the ionic liquid, not only the light transmittance is effectively enhanced, the detection rate of the photodetector is improved, but also the mechanical robustness and physicochemical stability of the polymer surface are improved by thermal cross-linking.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A flexible photodetector based on organic semiconductors comprises, from bottom to top, a porous anti-reflection film, a flexible transparent substrate, a flexible transparent cathode, a cathode buffer layer, a photoactive layer, an anode buffer layer and an anode; the porous anti-reflection film is prepared on the back of the flexible transparent substrate by spin coating, thermal crosslinking and deionized liquid.

[0008] Specifically, the preparation material of the antireflection film is prepared by mixing a polymer, an ionic liquid and a crosslinking agent; the polymer is one of polystyrene-b-polyethylene oxide-b-polystyrene, polystyrene-b-polymethyl methacrylate-b-polystyrene, polystyrene-b-polyethyl acrylate-b-polystyrene, poly-N-isopropylacrylamide-b-polyethylene oxide-b-poly-N-isopropylacrylamide), polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene); the ionic liquid is at least one of 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt, 1-ethyl-3-methylimidazole bismonofluorosulfonyl imide salt, 1-ethyl-3-methylimidazole dicyanamide salt, 1-butyl-3-methylimidazole hexafluorophosphate, and 1-butyl-3-methylimidazole tetrafluoroborate; the crosslinking agent is at least one of a bis-nitrogen heterocyclic crosslinking agent and a bis-azide crosslinking agent.

[0009] Preferably, the flexible transparent cathode is made of a material selected from the group consisting of silver nanowires, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, single-walled carbon nanotubes, and graphene.

[0010] Preferably, the cathode buffer layer is made of metal oxides, fullerenes 60 , fullerene derivatives, organic-inorganic hybrid electrolytes or conjugated polyelectrolytes.

[0011] Preferably, the photoactive layer is prepared from a mixed solution of an electron donor material and an acceptor material, and has a thickness ranging from 50 to 300 nm.

[0012] Preferably, the anode buffer layer is prepared from a material selected from the group consisting of transition metal oxides and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid.

[0013] Preferably, the anode is made of a material selected from the group consisting of Au, Ag, and graphene.

[0014] A method for preparing a flexible photodetector based on an organic semiconductor, the preparation process comprising the following steps:

[0015] Step 1: Clean the flexible transparent substrate with isopropyl alcohol and blow dry with nitrogen after cleaning;

[0016] Step 2: spin coating, printing or spraying a mixed chloroform solution of a polymer, an ionic liquid and a crosslinking agent on the back of the dried flexible transparent substrate, and then placing the substrate in a constant temperature box for thermal curing to form a crosslinked ion gel;

[0017] Step 3: Soak the cross-linked ion gel and the flexible transparent substrate after heat curing in chloroform for 10 seconds to remove the ionic liquid in the polymer to form a porous antireflection film, blow off the surface solvent with nitrogen gas and dry it;

[0018] Step 4: Spin-coating a transparent conductive cathode material on the surface of the flexible transparent substrate, and then baking at 100° C. for 5 minutes to remove the solvent, repeating three times to obtain a uniform flexible transparent cathode;

[0019] Step 5: spin coating, printing or spraying a cathode buffer layer solution on the surface of the flexible transparent cathode, and then performing thermal annealing to obtain a cathode buffer layer;

[0020] Step 6: Spin-coating the active layer mixed solution on the cathode buffer layer, and then performing thermal annealing to obtain a photoactive layer;

[0021] Step 7: At a vacuum degree of 1×10 -4 Under Pa conditions, MoO3 anode buffer layer was evaporated;

[0022] Step 8: At a vacuum degree of 1×10 -4 Pa conditions, the metal anode was evaporated.

[0023] Preferably, in step 2, thermal curing is performed at 190-210° C. for 30 min; in step 3, drying is performed at 90-100° C. for 2 min; and in step 5, annealing is performed at 150-250° C. for 10-20 min.

[0024] The beneficial effects of the present invention are as follows:

[0025] 1. A porous anti-reflection film is prepared by coating a mixed solution of polymer, ionic liquid and cross-linking agent on the back of a flexible transparent substrate. The morphology of the porous film can be easily controlled by adjusting the proportion of ionic liquid without transfer, effectively reducing the reflection, refraction and absorption of light at the substrate, enhancing the transmittance of light, allowing the incident light to be fully absorbed by the absorption layer, and improving the detection rate of the flexible organic photodetector.

[0026] 2. By coating a layer of thermally cross-linked porous anti-reflection film on the back of a flexible transparent substrate, the chemical cross-linking between polymer films can effectively enhance the firmness and physicochemical stability of the porous structure during stretching. At the same time, this layer of stretchable porous anti-reflection film protects the flexible substrate and is suitable for large-scale integration of flexible electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the proportional relationship of the various components in the drawings of this specification does not represent the proportional relationship in actual material selection and design, which is only a schematic diagram of the structure or position, wherein:

[0028] Figure 1 It is a schematic diagram of the structure of the present invention;

[0029] Figure 2 Schematic diagram of the structure of the porous antireflection film in the present invention;

[0030] Description of the reference numerals in the accompanying drawings:

[0031] 1-porous antireflection film, 2-flexible transparent substrate, 3-flexible transparent cathode, 4-cathode buffer layer, 5-photoactive layer, 6-anode buffer layer, 7-anode. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.

[0033] The present invention is described in detail below in conjunction with the drawings.

[0034] like Figure 1 and Figure 2 As shown, a flexible photodetector based on organic semiconductors comprises, from bottom to top, a porous anti-reflection film 1, a flexible transparent substrate 2, a flexible transparent cathode 3, a cathode buffer layer 4, a photoactive layer 5, an anode buffer layer 6 and an anode 7; the porous anti-reflection film 1 is prepared on the back of the flexible transparent substrate 2 by spin coating, thermal crosslinking and deionized liquid; the thermally crosslinked porous anti-reflection film solution is mixed with a polymer, an ionic liquid and a bis-nitrogen heterocyclic crosslinker or a bis-azide crosslinker in a certain proportion; the porous film is formed by washing away the uncrosslinked ionic liquid in the thermally crosslinked mixture by chloroform.

[0035] The material of the antireflection film 1 is prepared by mixing a polymer, an ionic liquid and a crosslinking agent; the polymer is polystyrene-b-polyethylene oxide-b-polystyrene (PS-PEO-PS), polystyrene-b-polymethyl methacrylate-b-polystyrene (PS-PMMA-PS), polystyrene-b-polyethyl acrylate-b-polystyrene (PS-PEA-PS), poly-N-isopropylacrylamide-b-polyethylene oxide-b-poly-N-isopropylacrylamide), polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) The ionic liquid is at least one of 1-ethyl-3-methylimidazolium trifluoromethanesulfonyl imide ([EMIM][TFSI]), 1-ethyl-3-methylimidazolium bismonofluorosulfonyl imide ([EMIM][FSI]), 1-ethyl-3-methylimidazolium dicyanamide ([EMIM][DCA]), 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6]), and 1-butyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF4]); the cross-linking agent is at least one of a bis-nitrogen heterocyclic cross-linking agent and a bis-azide cross-linking agent.

[0036] The material of the flexible transparent electrode 3 is one of silver nanowires (AgNWs), poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), single-walled carbon nanotubes (SWCNT), and graphene.

[0037] The cathode buffer layer 4 is made of metal oxides (ZnO, TiO x , SnO2), fullerene C 60 , fullerene derivatives, organic-inorganic hybrid electrolytes or conjugated polyelectrolytes.

[0038] The photoactive layer 5 is prepared from a mixed solution of an electron donor material and an acceptor material, and has a thickness ranging from 50 to 300 nm.

[0039] The anode buffer layer 6 is made of transition metal oxides (MoO3, WO x , NiO x ) or poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS).

[0040] The anode 7 is made of a material selected from the group consisting of Au, Ag, and graphene.

[0041] A method for preparing a flexible photodetector based on an organic semiconductor, the preparation process comprising the following steps:

[0042] Step 1: Clean the flexible transparent substrate 2 with isopropyl alcohol and blow dry with nitrogen after cleaning;

[0043] Step 2: spin coating, printing or spraying a mixed chloroform solution of a polymer, an ionic liquid and a crosslinking agent on the back of the dried flexible transparent substrate 2, and then placing the substrate in a constant temperature box for thermal curing to form a crosslinked ion gel; the thermal curing is carried out at 190-210° C. for 30 minutes;

[0044] Step 3: Soak the cross-linked ion gel and the flexible transparent substrate 2 after heat curing in chloroform for 10 seconds to remove the ionic liquid in the polymer to form a porous antireflection film 1, blow off the surface solvent with nitrogen and then dry; the drying is carried out at 90-100° C. for 2 minutes;

[0045] Step 4: Spin-coating a transparent conductive cathode material on the surface of the flexible transparent substrate 2, and then baking at 100° C. for 5 minutes to remove the solvent, and repeating this process three times to obtain a uniform flexible transparent cathode 3;

[0046] Step 5: spin coating, printing or spraying a cathode buffer layer solution on the surface of the flexible transparent cathode 3, and then performing thermal annealing to obtain a cathode buffer layer 4; the annealing is performed at 150 to 250° C. for 10 to 20 minutes;

[0047] Step 6: spin-coating the active layer mixed solution on the cathode buffer layer 4, and then performing thermal annealing to obtain the photoactive layer 5;

[0048] Step 7: At a vacuum degree of 1×10 -4 Under Pa conditions, MoO3 anode buffer layer 6 was evaporated;

[0049] Step 8: At a vacuum degree of 1×10 -4 Pa conditions, the metal anode 7 is evaporated.

[0050] Embodiment 1 (control group):

[0051] 1. Clean the flexible transparent substrate with isopropanol and blow dry with clean nitrogen after cleaning;

[0052] 2. The transparent conductive cathode material AgNWs ethanol dispersion was diluted to 2 mg / mL with deionized water and isopropanol (1:4), and AgNWs were spin-coated on the surface of the flexible transparent substrate (2000 rpm, 40 s), and then baked at 100 ° C for 10 min to remove the solvent in the AgNWs. This was repeated three times to obtain a transparent and uniform AgNW with a resistance as low as about 20 Ωsq -1 Conductive film for resistors (80 μm);

[0053] 3. Spin-coat ZnO sol on the surface of the transparent conductive cathode to prepare a cathode buffer layer (3000 rpm, 50 s, 30 nm), and perform thermal annealing on the formed film (150 ° C, 15 min);

[0054] 4. In a glove box, an active layer of PM6:Y6 (mass ratio PM6:Y6=1:1.2, PM6 6 mg / mL) was dissolved in a mixed solvent of chloroform and 1-chloronaphthalene (volume 0.5%) and spin-coated on the ZnO buffer layer (3000 rpm, 30 s), followed by thermal annealing (100 °C, 10 min);

[0055] 5. At a vacuum degree of 1×10 -4 MoO3 (10 nm) was evaporated under Pa conditions;

[0056] 6. At a vacuum degree of 1×10 -4 Au metal anode (80 nm) was evaporated under Pa conditions;

[0057] 7. Under standard test conditions: AM 1.5, 100mW / cm 2 , the dark current of the device (J d )=1.3×10 -8 A / cm 2 , photocurrent (J ph )=2.5×10 -2 mA / cm 2 , specific detection rate (D * )=2.46×10 11 Jones;

[0058] 8. The specific detection rate (D * )=1.89×10 11 Jones, retaining 76.83% conversion efficiency.

[0059] Embodiment 2:

[0060] 1. Clean the flexible transparent substrate with isopropanol and blow dry with clean nitrogen after cleaning;

[0061] 2. Spin-coat a mixed chloroform solution of PS-PEO-PS triblock polymer, [EMIM][TFSI] ionic liquid and DA cross-linking agent (mass ratio PS-PEO-PS: [EMIM][TFSI]: DA: chloroform = 3:15:1:150, 5000 rpm, 60 s, 80 nm) on the back of the dried substrate, and then place it in a 200 ° C constant temperature box for 30 min for thermal curing to form a cross-linked ion gel;

[0062] 3. Soak the cross-linked ion gel / substrate after thermal curing in chloroform for 10 seconds, blow off the surface solvent with nitrogen and then dry (100°C, 2 minutes);

[0063] 4. The transparent conductive cathode material AgNWs ethanol dispersion was diluted to 2 mg / mL with deionized water and isopropanol (1:4), and AgNWs were spin-coated on the surface of the flexible transparent substrate (2000 rpm, 40 s), and then baked at 100 ° C for 10 min to remove the solvent in the AgNWs. This was repeated three times to obtain a transparent and uniform AgNW with a resistance as low as about 20 Ωsq -1 Conductive film for resistors (80 μm);

[0064] 5. Spin-coat ZnO sol on the surface of the transparent conductive cathode to prepare a cathode buffer layer (3000 rpm, 50 s, 30 nm), and perform thermal annealing on the formed film (150 ° C, 15 min);

[0065] 6. In a glove box, an active layer of PM6:Y6 (mass ratio PM6:Y6=1:1.2, PM6 6 mg / mL) was dissolved in a mixed solvent of chloroform and 1-chloronaphthalene (volume 0.5%) and spin-coated on the ZnO buffer layer (3000 rpm, 30 s) and then thermally annealed (100 °C, 10 min);

[0066] 7. At a vacuum degree of 1×10 -4 MoO3 (10 nm) was evaporated under Pa conditions;

[0067] 8. At a vacuum degree of 1×10 -4 Under Pa conditions, metal anode Au (80nm) was evaporated;

[0068] 9. Under standard test conditions: AM 1.5, 100mW / cm 2 , the dark current of the device (J d )=1.2×10 -8 A / cm 2 , photocurrent (J ph )=3.7×10 -2 mA / cm 2 , specific detection rate (D * )=3.38×10 11 Jones;

[0069] 10. The specific detection rate (D * )=2.91×10 11 Jones, retaining 86.09% conversion efficiency.

[0070] Embodiment 3:

[0071] 1. Clean the flexible transparent substrate with isopropanol and blow dry with clean nitrogen after cleaning;

[0072] 2. Spin-coat a mixed chloroform solution of PS-PEO-PS triblock polymer, [EMIM][TFSI] ionic liquid and DA cross-linking agent (mass ratio PS-PEO-PS: [EMIM][TFSI]: DA: chloroform = 3:21:1:150, 5000 rpm, 60 s, 80 nm) on the back of the dried substrate, and then place it in a 200 ° C constant temperature box for 30 min for thermal curing to form a cross-linked ion gel;

[0073] 3. Soak the cross-linked ion gel / substrate after thermal curing in chloroform for 10 seconds, blow off the surface solvent with nitrogen and then dry (100°C, 2 minutes);

[0074] 4. The transparent conductive cathode material AgNWs ethanol dispersion was diluted to 2 mg / mL with deionized water and isopropanol (1:4), and AgNWs were spin-coated on the surface of the flexible transparent substrate (2000 rpm, 40 s), and then baked at 100 ° C for 10 min to remove the solvent in the AgNWs. This was repeated three times to obtain a transparent and uniform AgNW with a resistance as low as about 20 Ωsq -1 Conductive film for resistors (80 μm);

[0075] 5. Spin-coat ZnO sol on the surface of the transparent conductive cathode to prepare a cathode buffer layer (3000 rpm, 50 s, 30 nm), and perform thermal annealing on the formed film (150 ° C, 15 min);

[0076] 6. In a glove box, an active layer of PM6:Y6 (mass ratio PM6:Y6=1:1.2, PM6 is 6 mg / mL) was dissolved in a mixed solvent of chloroform and 1-chloronaphthalene (volume 0.5%) and spin-coated on the ZnO buffer layer (3000 rpm, 30 s), followed by thermal annealing (100 °C, 10 min);

[0077] 7. At a vacuum degree of 1×10 -4 MoO3 (10 nm) was evaporated under Pa conditions;

[0078] 8. At a vacuum degree of 1×10 -4 Under Pa conditions, metal anode Au (80nm) was evaporated;

[0079] 9. Under standard test conditions: AM 1.5, 100mW / cm 2 , the dark current of the device (J d )=1.3×10 -8 A / cm 2 , photocurrent (J ph )=4.2×10 -2 mA / cm 2 , specific detection rate (D * )=4.54×1011 Jones;

[0080] 10. The specific detection rate (D * )=3.96×10 11 Jones, retaining 87.22% conversion efficiency.

[0081] Embodiment 4:

[0082] 1. Clean the flexible transparent substrate with isopropanol and blow dry with clean nitrogen after cleaning;

[0083] 2. Spin-coat a mixed chloroform solution of PS-PEO-PS triblock polymer, [EMIM][TFSI] ionic liquid and DA cross-linking agent (mass ratio PS-PEO-PS: [EMIM][TFSI]: DA: chloroform = 3:27:1:150, 5000 rpm, 60 s, 80 nm) on the back of the dried substrate, and then place it in a 200 ° C constant temperature box for 30 min for thermal curing to form a cross-linked ion gel;

[0084] 3. Soak the cross-linked ion gel / substrate after thermal curing in chloroform for 10 seconds, blow off the surface solvent with nitrogen and then dry (100°C, 2 minutes);

[0085] 4. The transparent conductive cathode material AgNWs ethanol dispersion was diluted to 2 mg / mL with deionized water and isopropanol (1:4), and AgNWs were spin-coated on the surface of the flexible transparent substrate (2000 rpm, 40 s), and then baked at 100 ° C for 10 min to remove the solvent in the AgNWs. This was repeated three times to obtain a transparent and uniform AgNW with a resistance as low as about 20 Ωsq -1 Conductive film for resistors (80 μm);

[0086] 5. Spin-coat ZnO sol on the surface of the transparent conductive cathode to prepare a cathode buffer layer (3000 rpm, 50 s, 30 nm), and perform thermal annealing on the formed film (150 ° C, 15 min);

[0087] 6. In a glove box, an active layer of PM6:Y6 (mass ratio PM6:Y6=1:1.2, PM6 is 6 mg / mL) was dissolved in a mixed solvent of chloroform and 1-chloronaphthalene (volume 0.5%) and spin-coated on the ZnO buffer layer (3000 rpm, 30 s), followed by thermal annealing (100 °C, 10 min);

[0088] 7. At a vacuum degree of 1×10 -4 Under Pa conditions, MoO3 anode buffer layer (10 nm) was evaporated;

[0089] 8. At a vacuum degree of 1×10-4 Under Pa conditions, metal anode Au (80nm) was evaporated;

[0090] 9. Under standard test conditions: AM 1.5, 100mW / cm 2 , the dark current of the device (J d )=1.2×10 -8 A / cm 2 , photocurrent (J ph )=4.0×10 -2 mA / cm 2 , specific detection rate (D * )=3.71×10 11 Jones;

[0091] 10. The specific detection rate (D * )=3.14×10 11 Jones, retaining 84.64% conversion efficiency.

[0092] It can be seen from Examples 2-4 that the flexible organic photodetector prepared according to a method for preparing a flexible photodetector based on an organic semiconductor comprises, from bottom to top, a porous anti-reflection film 1, a flexible transparent substrate 2, a flexible transparent cathode 3, a cathode buffer layer 4, a photoactive layer 5, an anode buffer layer 6 and an anode 7; the thermally cross-linked porous anti-reflection film is prepared on the back of the flexible transparent substrate by spin coating and thermal cross-linking; the thermally cross-linked porous anti-reflection film solution is mixed by a polymer, an ionic liquid and a bis-nitrogen heterocyclic cross-linking agent or a bis-azide cross-linking agent in a certain proportion; the ionic liquid in the mixture film that is not thermally cross-linked is washed away by chloroform to form a porous film.

[0093] The flexible photodetector prepared by introducing a thermally cross-linked porous anti-reflection film on the back of the flexible transparent substrate (i.e., the flexible organic photodetector prepared in Examples 2 to 4) has a significantly higher J value than the flexible photodetector prepared without treatment (i.e., the flexible photodetector prepared in Example 1). ph Increase, D * This is because the porous antireflection film is prepared by coating a mixed solution of polymer, ionic liquid and cross-linking agent on the back of the flexible substrate, and the surface microstructure of the porous film can be easily controlled by adjusting the proportion of ionic liquid without transfer printing (such as Figure 2As shown in the figure, the reflection, refraction and absorption of light at the substrate are effectively reduced, the transmittance of light is enhanced, the incident light is fully absorbed by the absorption layer, and the detection rate of the flexible organic photodetector is improved. Secondly, by coating a layer of thermally cross-linked porous anti-reflection film on the back of the flexible substrate, the chemical cross-linking between the polymer films can effectively enhance the stability and physicochemical stability of the porous structure when stretched. At the same time, the layer of stretchable porous anti-reflection film protects the flexible substrate and is suitable for large-scale integration of flexible electronics.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A flexible photodetector based on organic semiconductor, characterized in that: The invention comprises, from bottom to top, a porous anti-reflection film (1), a flexible transparent substrate (2), a flexible transparent cathode (3), a cathode buffer layer (4), a photoactive layer (5), an anode buffer layer (6) and an anode (7); the porous anti-reflection film (1) is prepared on the back of the flexible transparent substrate (2) by spin coating, thermal crosslinking and deionized liquid.

2. The flexible photodetector based on organic semiconductor according to claim 1, characterized in that: The antireflection film (1) is prepared by mixing a polymer, an ionic liquid and a crosslinking agent; the polymer is one of polystyrene-b-polyethylene oxide-b-polystyrene, polystyrene-b-polymethyl methacrylate-b-polystyrene, polystyrene-b-polyethyl acrylate-b-polystyrene, poly-N-isopropylacrylamide-b-polyethylene oxide-b-poly-N-isopropylacrylamide), polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene); the ionic liquid is at least one of 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt, 1-ethyl-3-methylimidazole bismonofluorosulfonyl imide salt, 1-ethyl-3-methylimidazole dicyanamide salt, 1-butyl-3-methylimidazole hexafluorophosphate, and 1-butyl-3-methylimidazole tetrafluoroborate; the crosslinking agent is at least one of a bis-nitrogen heterocyclic crosslinking agent and a bis-azide crosslinking agent.

3. The flexible photodetector based on organic semiconductor according to claim 1, characterized in that: The flexible transparent cathode (3) is prepared from a material selected from the group consisting of silver nanowires, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, single-walled carbon nanotubes, and graphene.

4. The flexible photodetector based on organic semiconductor according to claim 1, characterized in that: The cathode buffer layer (4) is made of metal oxides, fullerene C 60 , fullerene derivatives, organic-inorganic hybrid electrolytes or conjugated polyelectrolytes.

5. The flexible photodetector based on organic semiconductor according to claim 1, characterized in that: The photoactive layer (5) is prepared from a mixed solution of an electron donor material and an acceptor material, and has a thickness ranging from 50 to 300 nm.

6. The flexible photodetector based on organic semiconductor according to claim 1, characterized in that: The anode buffer layer (6) is prepared from a material selected from the group consisting of a transition metal oxide and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid.

7. The flexible photodetector based on organic semiconductor according to claim 1, characterized in that: The anode (7) is made of a material selected from the group consisting of Au, Ag, and graphene.

8. A method for preparing a flexible photodetector based on an organic semiconductor, characterized in that: The preparation process includes the following steps: Step 1: Clean the flexible transparent substrate (2) with isopropyl alcohol, and then dry it with nitrogen gas; Step 2: spin coating, printing or spraying a mixed chloroform solution of a polymer, an ionic liquid and a cross-linking agent on the back of the dried flexible transparent substrate (2), and then placing the substrate in a constant temperature box for thermal curing to form a cross-linked ion gel; Step 3: soaking the cross-linked ion gel and the flexible transparent substrate (2) after heat curing in chloroform for 10 seconds to remove the ionic liquid in the polymer to form a porous antireflection film (1), blowing off the surface solvent with nitrogen and then drying; Step 4: Spin-coating a transparent conductive cathode material on the surface of the flexible transparent substrate (2), and then baking at 100° C. for 5 minutes to remove the solvent, and repeating this process three times to obtain a uniform flexible transparent cathode (3); Step 5: spin coating, printing or spraying a cathode buffer layer solution on the surface of the flexible transparent cathode (3), and then performing thermal annealing to obtain a cathode buffer layer (4); Step 6: Spin-coating the active layer mixed solution onto the cathode buffer layer (4), and then performing a thermal annealing treatment to obtain a photoactive layer (5); Step 7: At a vacuum degree of 1×10 -4 Under Pa conditions, a MoO3 anode buffer layer (6) is evaporated; Step 8: At a vacuum degree of 1×10 -4 Pa conditions, a metal anode (7) is evaporated.

9. The method for preparing a flexible photodetector based on an organic semiconductor according to claim 8, characterized in that: In step 2, thermal curing is performed at 190-210° C. for 30 minutes; in step 3, drying is performed at 90-100° C. for 2 minutes; in step 5, annealing is performed at 150-250° C. for 10-20 minutes.

Citation Information

Patent Citations

  • Photoelectric detector, manufacturing method thereof and photoelectric detector fabric

    CN108155294A

  • Flexible stretchable photoelectric detector with adjustable spectral range and preparation method thereof

    CN114335347A